Epigenetic Downregulation of FASN in Visceral Adipose Tissue of Insulin Resistant Subjects - Sievert, Helen; Krause, Christin; Geißler, Cathleen; Grohs, Martina; El-Gammal, Alexander T; Wolter, Stefan; Mann, Oliver; Lehnert, Hendrik; Kirchner, Henriette (Experimental and clinical endocrinology & diabetes, 2021)
The risk to develop type 2 diabetes increases with the amount of visceral adiposity presumably due to increased lipolysis and subsequent lipid accumulation in visceral organs. However, data describing the molecular regulation of these pathways in humans are rare. We tested if genes of the lipogenic and lipolytic pathways are associated with glucose intolerance independently of obesity in visceral adipose tissue (VAT) of obese subjects. Moreover, we studied DNA methylation of ( that catalyses the synthesis of long-chain fatty acids, in VAT of the same subjects and whether it is associated with metabolic traits. Visceral adipose tissue biopsies and blood samples were taken from 93 severely obese subjects undergoing bariatric surgery. Subjects were grouped in low HbA1c (L-HbA1c, HbA1c<6.5 %) and high HbA1c (H-HbA1c, HbA1c≥6.5 %) groups and expression of genes from the lipogenic and lipolytic pathways was analysed by TaqMan qPCR. DNA methylation of was quantified by bisulfite-pyrosequencing. expression was downregulated in visceral fat from subjects with high HbA1c (p = 0.00009). Expression of other lipogenetic ( , ) or lipolytic genes ( , ) and was not changed. DNA methylation of was increased at a regulatory ChoRE recognition site in the H-HbA1c-subgroup and correlated negatively with mRNA (r = - 0.302, p = 0.0034) and positively with HbA1c (r = 0.296, p = 0.0040) and blood glucose (r = 0.363, p = 0.0005). Epigenetic downregulation of in visceral adipose tissue of obese subjects might contribute to limited lipogenesis of important insulin sensitizing fatty acids and could thereby contribute to glucose intolerance and the development of type 2 diabetes independently of obesity.